ANALISIS SOAL KETERAMPILAN PROSES SAINS (KPS) PADA MATERI BIOLOGI DI SMA KOTA PALEMBANG - Jita Purnamasari; Sri Wardhani; Sulton Nawawi (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2021)
Science process skills is the ability of students to apply scientific methods in understanding, developing science and discovering knowledge. The purpose of this study was to determine the percentage of questions for each Science process skills indicator on biology material in Senior High School at Palembang. The research method was used descriptive was qualitative. The sampling technique used purposive sampling. The sample used was the odd semester final exam questions in Senior Hight School Palembang. The instruments was used in the study were tests and non-tests. Non-test instruments in the form of interview sheets, questionnaire sheets, observation sheets and documentation. The test instrument was used the class X odd semester final exam question instrument made by the teacher. The technique for analyzing the data was used percentage technique. The results obtained from the analysis of semester final exam odd questions for the 2019/2020 year school in Palembang High School, there were 4 Science process skills indicators that were applied to the question instrument with a deficient category consisting of observing indicators (6.32%), grouping indicators (18.02 %), the indicators predict / predict (3.75%) and the indicators plan the experiment (2.50%), while the indicators interpret, ask questions, hypothesize, apply concepts and communicating (0%) in the poor category. The analysis of Science process skills questions on biology material in Senior High School in Palembang was categorized as lacking because the school had not fully made the Science process skills based question instrument and the questions made on average were still at the cognitive limit.